Detailed microstructural and mechanical evaluation of yttria-stabilized zirconia-Ti composite compacts developed using spark plasma and electric discharge sintering processes. Issue 21 (1st November 2022) - Jeong, C.H.; Vijayakumar, E.; Lee, H.G.; Lee, W.H.
Abstract: In this work, electric discharge sintering (EDS) and spark plasma sintering (SPS) methods are used to fabricate different yttria-stabilized zirconia–titanium (YSZ-Ti) composite compacts. The compacts were prepared using the ball-milled precursors and by varying the YSZ content of the YSZ-Ti composite (0, 1, 3, 5, 10 wt%). Then, the microstructures and mechanical properties of these composite compacts are analyzed in detail and compared. The results indicated that the YSZ contents of the SPS produced composite compacts are agglomerated and dispersed mostly at the Ti particle boundaries, according to the microstructural analyses. In the EDS composite compacts, the YSZ component is uniformly distributed throughout the Ti matrix. As a result, the mechanical properties such as the hardness (from 88 HV to 611 HV), yield strength (366 MPa–922 MPa), and tensile strength (from 743 MPa to 1944 MPa) of the EDS composite compacts are improved significantly. In comparison, as the YSZ content of Ti increased, the mechanical properties of the SPS prepared composite compacts are also enhanced but not as much as those of the EDS processed composite compacts (hardness (from 219 HV to 382 HV), yield strength (321 MPa–502 MPa), and tensile strength (from 692 MPa to 1076 MPa). To summarize, a composite comprising a Ti matrix reinforced with YSZ was efficiently fabricated by EDS rather than by SPS using Ti powder with surface-embedded YSZ. The excellent mechanical properties of the Ti-YSZ composites fabricated by EDS can be ascribed to the uniform and homogeneous distribution of YSZ in the Ti matrix phase. EDS is thus a promising powder metallurgy technique for the production of low-cost isotropic Ti matrix composites reinforced with ceramic particles.